Enumeration of Antibacterial Activity of Few Medicinal Plants by Bioassay Method - B. Uma Reddy (E-Journal of Chemistry)
The present study was aimed to investigate the antibacterial activity of some common locally available plants, in order to estimate the biological potential of these herbs. The alcoholic extract of Tagetes erecta L (Asteraceae), Argemone mexicana L (Papavaraceae), Datura stramonium L. (Solanaceae) and Tylophora indica (Burm.f.) Merr. (Asclepiadaceae) were evaluated for antibacterial activity using broth dilution bioassay method. It is clear from the results that, the extracts of these plants acts as a good source of antibiotics against various bacterial pathogens tested and exhibited broad spectrum of antibacterial activity. These plant extracts were shown to be moderate to maximum inhibitory effect against different bacterial forms such as Salmonella typhii, Proteus vulgaris, Pseudomonas aeruginosa and Escherichia coli, where as, mild to moderate activity against Klebsiella pneumoniae and Staphylococcus aureus. The results of these studies revealed most valuable information and also support the continued sustainable use of these plants in traditional systems of medicine.